2020
DOI: 10.1126/sciadv.abc3598
|View full text |Cite
|
Sign up to set email alerts
|

Two replication fork remodeling pathways generate nuclease substrates for distinct fork protection factors

Abstract: Fork reversal is a common response to replication stress, but it generates a DNA end that is susceptible to degradation. Many fork protection factors block degradation, but how they work remains unclear. Here, we find that 53BP1 protects forks from DNA2-mediated degradation in a cell type–specific manner. Fork protection by 53BP1 reduces S-phase DNA damage and hypersensitivity to replication stress. Unlike BRCA2, FANCD2, and ABRO1 that protect reversed forks generated by SMARCAL1, ZRANB3, and HLTF, 53BP1 prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
94
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(100 citation statements)
references
References 53 publications
6
94
0
Order By: Relevance
“…Further supporting this scenario, 53BP1 has been shown to physically accumulate at and protect stalled replication forks against nascent strand degradation [97,99]. Interestingly, the fork protection defect arising from 53BP1 loss is dependent on fork reversal by FBH1 but not SMARCAL1, ZRANB3, or HLTF [99]. Further clarification of which fork structures canonical DSB signaling proteins are recruited to and how they regulate the replication stress response upstream of fork breakage will be important, as it is currently unclear which of these factors are critical for mounting a successful response.…”
Section: Replication Fork Stability and Remodelingmentioning
confidence: 88%
See 1 more Smart Citation
“…Further supporting this scenario, 53BP1 has been shown to physically accumulate at and protect stalled replication forks against nascent strand degradation [97,99]. Interestingly, the fork protection defect arising from 53BP1 loss is dependent on fork reversal by FBH1 but not SMARCAL1, ZRANB3, or HLTF [99]. Further clarification of which fork structures canonical DSB signaling proteins are recruited to and how they regulate the replication stress response upstream of fork breakage will be important, as it is currently unclear which of these factors are critical for mounting a successful response.…”
Section: Replication Fork Stability and Remodelingmentioning
confidence: 88%
“…This could allow RNF168 to ubiquitylate H2A(X) in its native nucleosomal environment and thereby promote recruitment of 53BP1, which may shield fork intermediates from unfettered nucleolytic degradation, apparent upon depletion of RNF168 or 53BP1 [90]. Further supporting this scenario, 53BP1 has been shown to physically accumulate at and protect stalled replication forks against nascent strand degradation [97,99]. Interestingly, the fork protection defect arising from 53BP1 loss is dependent on fork reversal by FBH1 but not SMARCAL1, ZRANB3, or HLTF [99].…”
Section: Replication Fork Stability and Remodelingmentioning
confidence: 89%
“…The BRCA1 antagonist, 53BP1, has also been reported to play a role in fork protection, although this was not observed consistently between various groups ( 36–39 ). Recently, this contradiction was resolved by showing that the role of 53BP1 in fork protection is dependent on the chronic versus acute inactivation of 53BP1 ( 40 ). This suggested that distinct molecular pathways may exist for fork protection; indeed, the requirement of fork protection proteins depends on the pathway used in fork remodeling.…”
Section: Common Strategies To Deal With Replication Blocksmentioning
confidence: 99%
“…This suggested that distinct molecular pathways may exist for fork protection; indeed, the requirement of fork protection proteins depends on the pathway used in fork remodeling. Specifically, BRCA2, FANCD2, and ABRO1 protect forks generated by SMARCAL1, ZRANB3, and HLTF, whereas 53BP1, FANCA, FANCC, FANCG, BOD1L and VHL protect forks remodeled by FBH1 ( 40 ). Other proteins, including RADX, FBH1 and RAD52 prevent excessive fork reversal by negatively regulating RAD51 activity ( 41–43 ).…”
Section: Common Strategies To Deal With Replication Blocksmentioning
confidence: 99%
“…DNA2-dependent hyperresection has also been observed at de-protected stalled RFs in cells missing one of a group of proteins that have been shown to control nuclease access at stalled replication intermediates. Accordingly, DNA2 has been shown to drive excessive nascent-strand degradation in the absence of BRCA2, RIF1, BOD1L, FANCD2, ABRO1, and 53BP1 [ 126 , 127 , 128 , 129 , 130 , 131 , 132 ]. The pathological nature of stalled RF hyperresection is exemplified in a study showing that depletion of DNA2 suppresses the sensitivity of cells lacking fork-protection factor FANCD2 to replication-blocking DNA cross-linking agents [ 126 ].…”
Section: An Essential Role Of Human Dna2 In Rf Recovery?mentioning
confidence: 99%